2022
DOI: 10.1001/jamanetworkopen.2022.0548
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality Rates Among Hospitalized Patients With COVID-19 Infection Treated With Tocilizumab and Corticosteroids

Abstract: IMPORTANCE A World Health Organization (WHO) meta-analysis found that tocilizumab was associated with reduced mortality in hospitalized patients with COVID-19. However, uncertainty remains concerning the magnitude of tocilizumab's benefits and whether its association with mortality benefit is similar across respiratory subgroups. OBJECTIVE To use bayesian methods to assess the magnitude of mortality benefit associated with tocilizumab and the differences between respiratory support subgroups in hospitalized pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Our findings confirm that both baseline status at the start of tocilizumab treatment requiring IMV and hyperferritinemia are associated with poor outcome and add insight into predictors of tocilizumab failure in patients with SARS-CoV2 and SRF. This is in line with the Bayesian reanalysis of a previous meta-analysis of 15 studies of hospitalized patients with COVID-19 treated with tocilizumab and corticosteroids [ 53 ]. This study showed that simple oxygen therapy and non-invasive ventilation (NIV) was associated with a clinically significant mortality benefit of tocilizumab but not in patients with IMV.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings confirm that both baseline status at the start of tocilizumab treatment requiring IMV and hyperferritinemia are associated with poor outcome and add insight into predictors of tocilizumab failure in patients with SARS-CoV2 and SRF. This is in line with the Bayesian reanalysis of a previous meta-analysis of 15 studies of hospitalized patients with COVID-19 treated with tocilizumab and corticosteroids [ 53 ]. This study showed that simple oxygen therapy and non-invasive ventilation (NIV) was associated with a clinically significant mortality benefit of tocilizumab but not in patients with IMV.…”
Section: Discussionsupporting
confidence: 88%
“…The bDMARD tocilizumab, which blocks IL-6 signaling, garnered a lot of attention early during the COVID-19 pandemic, as IL-6 was noted to be elevated in the serum of severe COVID-19 patients [53]. Early reports suggested tociliuzumab treatment helped severe COVID-19 patients, and meta-analyses have demonstrated some benefit to those with severe COVID-19 pneumonia [54,55]. As soon as MIS-C was recognized as a SARS-CoV-2-associated illness, tocilizumab was also explored as a therapeutic option for children with refractory MIS-C [11 ▪▪ ,12].…”
Section: Biological Disease-modifying Antirheumatic Drug Use In Multi...mentioning
confidence: 99%
“…Bayesian analysis has also been used to elucidate the effect of interventions in specific subgroups, 10 to evaluate the effect of selection bias 33 and in metaanalysis. 34 This current analysis has several limitations which need to be addressed. First, some differences between studies concerning how PEEP and RM were used and titrated cannot be unraveled, although we will use a previously harmonized individual patient database.…”
Section: Discussionmentioning
confidence: 98%